Pengaruh Pengelolaan Modal Kerja terhadap Kinerja Keuangan: Studi Kasus PT. Pilar Jaya Konstruksi Periode 2021-2025 - M. Auriel Syira Ramadhan; Abdurrahim Abdurrahim; Siti Mardah (Yayasan Jompa Research and Development, 2026)
Delays in collecting receivables, accumulation of materials, and dependence on short-term loans can increase the risk of liquidity problems and reduce the profitability of construction companies, despite recording high revenues. This study aims to: (1) determine the effect of cash turnover on Return on Assets (ROA) at PT. Pilar Jaya Konstruksi; (2) analyze the effect of accounts receivable turnover on ROA; (3) examine the effect of inventory turnover on ROA; and (4) investigate the simultaneous effect of cash turnover, accounts receivable turnover, and inventory turnover on ROA. This research employs a quantitative approach with PT. Pilar Jaya Konstruksi, located in Tabalong Regency, South Kalimantan, as the research object. The study uses a total sampling technique, with secondary data consisting of 48 monthly financial reports, including balance sheets and income statements, covering the period from 2021 to 2025. Data were analyzed using descriptive statistics, classical assumption tests (normality, autocorrelation, multicollinearity, and heteroscedasticity), multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (Adjusted R Square). The results indicate that cash turnover has a significant effect on ROA (Sig. = 0.000 < 0.05). Accounts receivable turnover also significantly affects ROA (Sig. = 0.005 < 0.05), while inventory turnover shows a significant effect on ROA (Sig. = 0.000 < 0.05). Simultaneously, cash turnover, accounts receivable turnover, and inventory turnover significantly influence ROA. The Adjusted R Square value of 0.984 indicates that 98.4% of the variation in ROA can be explained by these three variables, while the remaining 1.6% is influenced by other factors outside the model.